The Urgency of Philosophical and Sociological Perspective on Educational Technology - Subkhan, Edi (Curriculum and Educational Technology Department, 2019)
In Indonesian context educational technology has been developed for years as a field of studies and profession (Subkhan, 2016). In many teacher colleges such as Universitas Negeri Jakarta (UNJ), Universitas Negeri Semarang (UNNES), Universitas Negeri Malang (UM) and Universitas Negeri Surabaya (Unesa) there were educational technology study programs, but until now the development of educational technology seems entrapped on its methodological and practical tendency. For instances how educational technology?s curricula?especially for bachelor degree?should meet with market demand, how practically and professionally facilitating learning process within and outside the schooling system, and how to strengthen the profession of educational technologist (see Haryono, Budisantoso, Subkhan, & Utanto, 2018).